Buckling analysis of a thin-walled structure using finite element method and design of experiments - Kamarudin, Mohamad Norfaieqwan; Syed Mohamed Ali, Jaffar; Aabid, Abdul; Ibrahim, Yasser E. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
In structural engineering, thin-walled structures play an important role in the design of the lightweight structural model. It carries different loading conditions when it exists in any model, and it is designed with thin plates or thin shells. Penetrating thin-walled structures with different kinds of holes can decrease their weight and facilitate repair and maintenance operations, such as those carried out for the wing of an airplane. In such applications, cutouts are often employed as part of the design of composite plates. Therefore, this paper attempted to design and analyse the thin-walled composite structure with a C-cross-section shape. To model and analyse the structures, a finite element method was utilized using the ABAQUS commercial tool, and the results of critical buckling load for different laminate types were obtained. Composite materials and structures have different parameters that can vary the results of analysis; therefore, to optimize the current mode a design of experiments method is used via MINITAB 20 and Design-Expert 13 tools. The selected parameters for this work were the opening ratio, spacing ratio, and shape of the hole for the output response as a critical buckling load was carried out. Based on the current results of simulation and optimization, it was found that the parameters of composite materials and structures will impact the output response, and the current study investigated the optimum parameters for the best possible outcome of the structural analysis.